2007
DOI: 10.4319/lo.2007.52.4.1645
|View full text |Cite
|
Sign up to set email alerts
|

Composition and degradation of marine particles with different settling velocities in the northwestern Mediterranean Sea

Abstract: Settling particles were collected from the Ligurian Sea in the northwestern Mediterranean Sea in May 2003 and separated by elutriation into different settling velocity classes (.230, 115-230, 58-115, and ,58 m d 21 ). Particles of the different classes were incubated for 5 d to study their biodegradability. Particulate opal content and organic compound composition (amino acids, pigments, lipids, and carbohydrates) were analyzed initially and at regular time intervals during the incubation period. Most particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 74 publications
9
65
0
Order By: Relevance
“…[22] Other studies [Goutx et al, 2007;Wakeham et al, 2009] reached the same conclusion after analyzing the composition of particles collected at 200 m in the Mediterranean Sea and separated by settling velocity. Samples from the Pacific Ocean also showed that material collected by in situ filtration, assumed to be suspended or with low settling rates, contained a remarkable abundance of labile organic compounds [Lee et al, 2000;Sheridan et al, 2002].…”
Section: Implications Of Slowly Settling Particles Dominating the Sizmentioning
confidence: 58%
“…[22] Other studies [Goutx et al, 2007;Wakeham et al, 2009] reached the same conclusion after analyzing the composition of particles collected at 200 m in the Mediterranean Sea and separated by settling velocity. Samples from the Pacific Ocean also showed that material collected by in situ filtration, assumed to be suspended or with low settling rates, contained a remarkable abundance of labile organic compounds [Lee et al, 2000;Sheridan et al, 2002].…”
Section: Implications Of Slowly Settling Particles Dominating the Sizmentioning
confidence: 58%
“…The data include observations from a range of named sediment-trap designs: moored automatic Kiel sediment traps (Bauerfeind et al, 2009;Bauerfeind and Nöthig, 2011), cone-shaped SMT 230 Kiel and Mark VI/V traps (Wefer and Fischer, 1993), cone-shaped multi-sampling SMT 230 KMU traps (Romero et al, 2002;Fahl and Nöthig, 2007), conical particle interceptor traps (Antia et al, 1999), conical sediment McLane Mark-7 traps (Hwang et al, 2009), drifting Technicap PPS 5 sediment traps (Goutx et al, 2000), Kiel HDW traps (Jonkers et al, 2010), large-aperture timeseries Kiel-type traps Iversen et al, 2010), Mark-VII automated sediment trap (CARI-ACO), McLane Mark 78G-21 (Jonkers et al, 2010), multisample moored conical traps (Bory et al, 2001), Parflux Mark 7G-13 time-series sediment trap (Honjo and Manganini, 1993;Jickells, 2003a, b, c, d;Lampitt et al, 2001Lampitt et al, , 2010, Aquatec Kiel-type sediment trap (Neuer et al, 1997(Neuer et al, , 2007, indented rotary sphere (IRS) settling velocity and time-series mode sediment traps (Peterson et al, 2005;Goutx et al, 2007;Lee et al, 2009a, b), SMT 234 Aquatec Meerestechnik Kiel trap (Helmke et al, 2005), surface-tethered particle interceptor traps (BATS), and PPS-5 traps (Jonkers et al, 2010). Information is sometimes insufficient to ascertain whether two models are identical.…”
Section: Sediment-trap Typesmentioning
confidence: 99%
“…Principal Components Analysis (PCA) is commonly used in the analysis of complex organic datasets (Goñi et al, 2000;Ingalls et al, 2006;Goutx et al, 2007). It is a multivariate regression analysis that reduces a large number of variables to a few principal components.…”
Section: Statistical Analyses (Pca)mentioning
confidence: 99%